If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(x-2)=3x-4x+5
We simplify the equation to the form, which is simple to understand
2(x-2)=3x-4x+5
Reorder the terms in parentheses
+(+2x-4)=3x-4x+5
Remove unnecessary parentheses
+2x-4=+3x-4x+5
We move all terms containing x to the left and all other terms to the right.
+2x-3x+4x=+5+4
We simplify left and right side of the equation.
+3x=+9
We divide both sides of the equation by 3 to get x.
x=3
| 2x+10=6x-4 | | 7-3(3)=-3+1 | | 17.50-8.75= | | (n+4)-(-3n-7)= | | k/15-13=4 | | 7k^2-54k-16= | | [7(z+5)-17]+[3(z-2)+2]= | | 19abc+18=62 | | 3t=3r-54 | | 12x-10-12=0 | | 10=4x+x^2 | | m=25(i) | | 5y+y-3=6y-5+6 | | 19abc=62 | | -6-(4-(2*4-(4-3)))= | | (n-4)-(-3n-7)= | | 2v^2+v-36= | | 1[1-7(2-6)]= | | 19abc*b=62 | | 49-14=5(x-5) | | x^2-14x+44=-4 | | 12(x+9)=-180 | | 9w-81= | | 3r+4s-6(4r-2s)= | | 4b+7b+6b-6= | | 20s^3+84s^2-80s= | | -10x-20=100 | | -6-4(4-(2-4-(4-3)))= | | 3r^2+14r-49= | | (4-2x)(8-2x)(x)=0 | | 3x+6=3x-4 | | d+di= |